Partisipasi Masyarakat Dalam Mewujudkan Gampong Mandiri Di Gampong Suak Puntong - Yulanda Arasih,; Reva Dwi Insari,; Nodi Marefanda, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The community as one of the subsystems of a village must be involved in the development process in the village. The involvement starts from the development planning stage, implementation, to the supervision stage. This research is entitled "Community Participation in Realizing an Independent Gampong in Suak Puntong Village" with the formulation of the problem in this study, namely how the community in realizing an independent village through infrastructure development in Suak Puntong Village and the purpose of this research is to determine community participation in realizing an independent village in Suak Puntong Village. Suak Puntong Village. From the results of the study, it can be concluded that in principle, community participation in the development of village infrastructure is very influential on the passage of a village infrastructure development process, especially in Suak Puntong Village, Kuala Pesisir District, Nagan Raya Regency, Development cannot run well, The level of community participation in Suak Village Puntong in the implementation of physical development is still considered low and the village government has made efforts and roles, such as inviting the community to participate in various village activities